2020
DOI: 10.1080/11038128.2020.1723686
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the contributing factors that influence the volition of adolescents with cerebral palsy: A directed content analysis

Abstract: Background: Communication, behavioural disturbances and low motivation influence the functional potential and the effectiveness of interventions in adolescents with cerebral palsy (CP). While the model of human occupation (MOHO) is a conceptual model in occupational therapy, no research on the volition of adolescents with CP in daily activities has been undertaken.Aim: To explore the elements contributing to the volition of adolescents with CP based on their own experienceMethods: A qualitative approach using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…An Australian study, involving 244 adults older than 70 years, demonstrated a significant association of volition with increased participation in physical activities in older adults living in the community [ 56 ]. Another study with adolescents with cerebral palsy demonstrated that occupational therapists can increase the motivation and will of this group through self-efficacy in interaction with environmental characteristics to promote personal causality [ 57 ]. Graff et al [ 58 ] found in their study of 135 couples of people with dementia and their caregivers that community OT improves the mood, quality of life and health of both people with dementia and their caregivers, improvement that was significant in the follow-up after 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…An Australian study, involving 244 adults older than 70 years, demonstrated a significant association of volition with increased participation in physical activities in older adults living in the community [ 56 ]. Another study with adolescents with cerebral palsy demonstrated that occupational therapists can increase the motivation and will of this group through self-efficacy in interaction with environmental characteristics to promote personal causality [ 57 ]. Graff et al [ 58 ] found in their study of 135 couples of people with dementia and their caregivers that community OT improves the mood, quality of life and health of both people with dementia and their caregivers, improvement that was significant in the follow-up after 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, we had restrictions in sampling in this group. Furthermore, an individual's interests are related to their values and environmental features [25]. The values of these individuals also could depend on their family and friends.…”
Section: Discussionmentioning
confidence: 99%
“…The Adolescent Interest Inventory-Cerebral Palsy (AII-CP): It is a 15-item self-report inventory, i.e. de-veloped by the first author of this research [25]; the findings of a qualitative study using directed content analysis and a Nominal Group Technique (NGT) were used for this purpose [26]. The Model of Human Occupation (MOHO), as an occupational therapy framework, was used for developing the AII-CP.…”
Section: Methodsmentioning
confidence: 99%
“…Participation is one of the outcomes of occupational therapy intervention and is defined as an engagement in daily life activities [2]. Participation has different aspects and depends on several factors, such as motivation and interest [3,4]. The difficulties in participation lead clients to occupational therapy [5].…”
Section: Introductionmentioning
confidence: 99%